Методичні підходи до забезпечення конкурентоспроможності підприємства меблевої промисловості - Шепелєва, Наталія Володимирівна; Скотнікова, Любов Петрівна (НТУ "ХПІ", 2017)
Результати дослідження наукових здобутків вчених з питань сутності конкурентоспроможності підприємства і методів її оцінки підтверджують важливість конкурентних позицій на ринку. Конкурентні переваги, якими володіють підприємства, дозволяють їм бути більш конкурентоспроможним серед підприємств. На основі аналізу ринку вітчизняної меблевої промисловості виявлені проблеми її розвитку. Запропоновані заходи підвищення конкурентоспроможності підприємства на ринку.

The reveal the factors that influence the development of the domestic furniture market. The concept of enterprise competitiveness by different scientists is revealed. It is told what competitive advantages the enterprise should have to ensure stable competitive positions in the market, the main principles of the enterprise competitiveness research. The factors of competitiveness offered by M. Porter are considers. Methods for assessing the competitiveness of an enterprise and ways to improve it are proposed. The description of the furniture market in Ukraine is presented. For example, one of the methods of assessing the competitiveness of the enterprise is presented - a polygon of competitiveness.
Methodical approaches to ensuring the competitiveness of the furniture industry enterprise
Keywords: конкурентні переваги; фактори конкурентоспроможності; методи оцінки конкурентоспроможності; ринок; меблевий бізнес; enterprise competitiveness; competitive advantages